MOTIVASI DAN HASIL BELAJAR AL-QUR’AN HADITS MELALUI MODEL PEMBELAJARAN BERBASIS PORTOFOLIO (STUDI PADA SANTRI MA’HAD ASSUNNAH TAHUN PELAJARAN 2022/2023) - MUHAMMAD TSALIS RAMADLANI, (UNISAN JURNAL, 2024)
Abstract Teachers play an important role in the teaching and learning process, they bear responsibility for the effectiveness of all educational efforts in schools, both in improving the quality of human resources, activities and student learning outcomes. In learning Al-Qur'an Hadith at Santri Ma’had Assunnah , there is still a lack of interaction between teachers and students. Conditions like this occur in almost every class, especially class X A. This can be seen when the teacher explains the recitation material, the class atmosphere is calm but tends to be tense. Students listen to the teacher's explanation calmly without daring to turn their heads, so that the teacher enthusiastically explains the subject matter without involving the students. Next, the formulation of this research problem is what is the motivation and results of learning Al-Qur'an Hadith. The aim of this research is to determine the motivation and outcomes of learning Al-Qur'an Hadith through a portfolio-based learning model at Santri Ma’had Assunnah . Meanwhile, this research uses descriptive qualitative research methods. Data collection was carried out using observation and documentation methods. Data analysis was carried out using triangulation, namely, data reduction, data display and verification. Based on the results of data analysis in the discussion of the previous chapter, it can be concluded that we are able to develop motivation and learning outcomes for Al-Qur'an Hadith through a portfolio-based learning model at Santri Ma’had Assunnah , namely by active student learning, cooperative student learning groups, creative teaching, discovery method and inquiry methodKeywords: Teacher Creativity, Motivation, and Learning Outcomes Keywords: Learning Motivation, Al-Qur'an Hadith Lessons